2014
DOI: 10.5005/jp-journals-10024-1559
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of a Home Bleaching Agent on Surface Characteristics of Indirect Esthetic Restorative Materials—Part II Microhardness

Abstract: The contact of home bleaching agents with esthetic restorative materials is unavoidable. Therefore protecting these restorations from bleaching agents and reglazing or at least polishing the restorations after bleaching is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…Passos and colleagues have shown that the concentration of bleaching agents and the type of ceramics significantly influence the changes in microhardness (Passos et al, 2010). Torabi et al depicted that the hardness of overglazed or polished surfaces is affected more by exposure to bleaching agents compared to autoglazed ceramic surfaces (Torabi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Passos and colleagues have shown that the concentration of bleaching agents and the type of ceramics significantly influence the changes in microhardness (Passos et al, 2010). Torabi et al depicted that the hardness of overglazed or polished surfaces is affected more by exposure to bleaching agents compared to autoglazed ceramic surfaces (Torabi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Microhardness has drawn much attention in the literature because it is an important physical characteristic of dental materials. 15-18 Hardness of a material has been defined as its resistance against permanent surface indentation or penetration; it depends on a material’s strength, ductility, elastic stiffness, plasticity, strain, toughness, viscoelasticity and viscosity. A material’s ability to abrade or its susceptibility to abrasion by opposing teeth, materials, or being softened by chemical agents has a role in the clinical durability of dental restorations.…”
Section: Discussionmentioning
confidence: 99%
“…Bu aktif bileşenler serbest radikal oluşturmadan kromojenleri okside etmektedir. 37 Son yıllarda yayımlanmış bir meta-analizde, farklı laboratuvar çalışmalarının sonuçlarını karşılaştırılmış, daha beyaz dişlere sahip olmak isteyen ve diş hekimine gitmeden hızlı ve kolay bir yöntem arayan hastaların sıklıkla başvurduğu bir yöntem olan hidrojen peroksit içermeyen OTC ürünler kullanılarak yapılan ağartma işlemlerinin, peroksit kullanılan ağartma işlemlerine göre ağartma etkisinin daha az olduğu bildirilmiştir. 38 OTC ürünlerinin satışı ve kullanımı gün geçtikçe artmasına karşın bu ürünlerle ilgili güvenilir bir araştırma protokolü ve ağartma etkinliği ve güvenilirliği ile ilgili çok az sayıda kanıt mevcuttur.…”
Section: Otc Ile Ağartma Yönteminin Kompozit Rezin Yüzey Sertliğine E...unclassified